Are prevention of mother-to-child HIV transmission service providers acquainted with national guideline recommendations? A cross-sectional study of primary health care centers in Lagos, Nigeria - B. Okusanya; C. Nweke; L. B. Gerald; S. Pettygrove; D. Taren; J. Ehiri (BMC, 2022)
Abstract Background Implementation of interventions for the prevention of mother-to-child transmission (PMTCT) of HIV in low- and middle-income countries, faces several barriers including health systems challenges such as health providers' knowledge and use of recommended guidelines. This study assessed PMTCT providers' knowledge of national PMTCT guideline recommendations in Lagos, Nigeria. Methods This was a cross-sectional survey of a purposive sample of twenty-three primary health care (PHC) centers in the five districts of Lagos, Nigeria. Participants completed a self-administered 16-item knowledge assessment tool created from the 2016 Nigeria PMTCT guidelines. Research Electronic Data Capture (REDCap) was used for data entry and R statistical software used for data analysis. The Chi square test with a threshold of P < 0.05 considered as significant was used to test the hypothesis that at least 20% of service providers will have good knowledge of the PMTCT guidelines. Results One hundred and thirteen (113) respondents participated in the survey. Most respondents knew that HIV screening at the first prenatal clinic was an entry point to PMTCT services (97%) and that posttest counselling of HIV-negative women was necessary (82%). Similarly, most respondents (89%) knew that early infant diagnosis (EID) of HIV should occur at 6-8 weeks of life (89%). However, only four (3.5%) respondents knew the group counselling and opt-out screening recommendation of the guidelines; 63% did not know that haematocrit check should be at every antenatal clinic visit. Forty-eight (42.5%) service providers had good knowledge scores, making the hypothesis accepted. Knowledge score was not influenced by health worker cadre (p = 0.436), training(P = 0.537) and professional qualification of ≤5 years (P = 0.43). Conclusion Service providers' knowledge of the PMTCT guidelines recommendations varied. The knowledge of group counselling and opt-out screening recommendations was poor despite the good knowledge of infant nevirapine prophylaxis. The findings highlight the need for training of service providers.